2016
DOI: 10.21071/ij21ce.v3i1.5645
|View full text |Cite
|
Sign up to set email alerts
|

L2 Writing Development: The Case of Two High-Achieving and Two Struggling College-Level Students

Abstract: Researchers and language practitioners have long been interested in the quest for theory-based, research-supported constructs that can adequately characterize L2 writing proficiency and development. The ongoing scholarly inquiry in this research area has led to the mounting recognition that complexity, accuracy and fluency (henceforth, CAF) constitute a conceptual framework capable of charting L2 writing proficiency and benchmarking development. Against this background, the present study aims to investigate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The result of the present study, similarly, dealt with the issue of engagement during out-of-class evaluation. The findings echoed a study by Zyad (2016) who found that while learning management systems (LMSs), such as MOODLE, can extend learners' discussions and course activities beyond class time, and enable continuous qualitative control of the mastering of the material, the patterns of engagement varied from high to poor. In similar vein, Sinaga and Pustika (2021) noted that despite MOODLE utilization getting favourable, learners find it difficult in the implementation of learning beyond classroom setting.…”
Section: Issues In Introducing the New Tools: Learning Engagementmentioning
confidence: 60%
See 1 more Smart Citation
“…The result of the present study, similarly, dealt with the issue of engagement during out-of-class evaluation. The findings echoed a study by Zyad (2016) who found that while learning management systems (LMSs), such as MOODLE, can extend learners' discussions and course activities beyond class time, and enable continuous qualitative control of the mastering of the material, the patterns of engagement varied from high to poor. In similar vein, Sinaga and Pustika (2021) noted that despite MOODLE utilization getting favourable, learners find it difficult in the implementation of learning beyond classroom setting.…”
Section: Issues In Introducing the New Tools: Learning Engagementmentioning
confidence: 60%
“…In fact, MOODLE offers features that can facilitate parent involvement in this process. Additionally, according to Zyad (2016), even an LMS can contribute to learner engagement in outside classroom activities, and engagement would be even greater if there were rewards for their invested efforts.…”
Section: Issues In Introducing the New Tools: Learning Engagementmentioning
confidence: 99%